Creación de una microempresa encargada del proceso manual y especializada en comercializar mango curtido en la ciudad de Guayaquil - Rivera Santana, María (2009)
Ecuador is a country rich in a flora and fauna for this reason one of the many fruit that in the country as is the mango. Ecuadorian fruit that have amount of nutrients which allow to compete with a large variety of tropical fruits. The mango is the fourth most traded tropical fruit in the world after bananas and pineapple. It is in the domestic and international market. In the season that produced this fruit many hawkers to expend on the streets of a not hygienic manner. And so the object this project is create a product hygienically prepared and processed with different standards for human consumption without the concern of contracting a disease but on the contrary that people can enjoy the mango tanning in salt and lemon in every month of year.